Variable immunogenicity of a vivax malaria blood-stage vaccine candidate. Issue 19 (6th May 2021) - De, Sai Lata; May, Samuel; Shah, Keshav; Slawinski, Michelle; Changrob, Siriruk; Xu, Shulin; Barnes, Samantha J.; Chootong, Patchanee; Ntumngia, Francis B.; Adams, John H.
Highlights: We evaluated the immunogenicity of a rDBPII vaccine with different variables. Significant variations in immune responses were observed with different variables. No specific pattern in immune responses with respect to sex or adjuvant observed. Sex and immune genes are critical variables to consider in vaccine study design. Abstract: Relapsing malaria caused by Plasmodium vivax is a neglected tropical disease and an important cause of malaria worldwide. Vaccines to prevent clinical disease and mosquito transmission of vivax malaria are needed to overcome the distinct challenges of this important public health problem. In this vaccine immunogenicity study in mice, we examined key variables of responses to a P. vivax Duffy binding protein vaccine, a leading candidate to prevent the disease-causing blood-stages. Significant sex-dependent differences were observed in B cell (CD80+) and T cell (CD8+) central memory subsets, resulting in significant differences in functional immunogenicity and durability of anti-DBP protective efficacy. These significant sex-dependent differences in inbred mice were in the CD73+CD80+ memory B cell, H2KhiCD38hi/lo, and effector memory subsets. This study highlights sex and immune genes as critical variables that can impact host responses to P. vivax antigens and must be taken into consideration when designing clinical vaccine studies.